Transformational Leadership, Digital Competence, and Adaptive Performance During Organizational Change: A Qualitative Case Study - Syah Abadi Mendrofa; Ferdinand Hasudungan Siagian; Adi Soeprapto; Susanti; Nazirwan (International Journal of Management and Business Economics, 2026)
This study examines how digital transformation prompts technology firms to enhance human resources so employees adapt to technological changes and dynamic business needs. Success in organizational change depends not only on technology adoption but also on transformational leadership, digital competence, adaptive performance, and organizational support. The research analyzes how these four factors interrelate during PT DOT Indonesia's digital transformation using a qualitative case study. Data were collected via in-depth interviews with 12 purposively sampled informants (HR Manager, HR Officer, Project Manager, Team Leader, Software Engineer, UI/UX Designer, QA Engineer, Business Analyst, DevOps Engineer, and Mobile Developer). Data analysis followed Miles, Huberman, and Saldaña's interactive model through data condensation, display, and conclusion drawing, with open, axial, and selective coding. Findings show transformational leadership fosters continuous learning through coaching, empowerment, participation, and mentoring. Digital competence grows via self-directed learning, knowledge sharing, and technical mentoring, enhancing employees' ability to handle project changes and technological developments. Adaptive performance appears as flexibility, learning agility, problem-solving, and responsiveness to client needs. Organizational support through training, learning culture, sharing sessions, and collaboration strengthens employee readiness. The study indicates that the synergy among these factors is crucial for navigating digital transformation in technology-based companies.